Perceived Stress and Smartphone Addiction in Medical College Students: The Mediating Role of Negative Emotions and the Moderating Role of Psychological Capital - Wang, Wenbo; Mehmood, Anam; Li, Ping; Yang, Zhaonan; Niu, Jinbao; Chu, Haiyun; Qiao, Zhengxue; Qiu, Xiaohui; Zhou, Jiawei; Yang, Yanjie; Yang, Xiuxian (Frontiers in Psychology, 2021)
Background: Many studies have confirmed the existence of an extremely close relationship between smartphone addiction and perceived stress. However, the mediating and moderating mechanisms underlying the association between perceived stress and smartphone addiction in medical college students remain largely unexplored. Methods: A questionnaire was distributed among a total of 769 medical college students in Heilongjiang Province, China. Participants completed measures of perceived stress, smartphone addiction, negative emotions and psychological capital. Pearson correlation analysis was used to test correlations between variables. The analysis of moderated mediation model was performed using Hayes’s PROCESS macro. Results: Pearson correlation analysis indicated perceived stress (r = 0.18, p < 0.01) and negative emotions (r = 0.31, p < 0.01) were positively correlated with smartphone addiction, and psychological capital was negatively correlated with smartphone addiction (r = − 0.29, p < 0.01). The moderated mediation analysis indicated that negative emotions partially mediated the association between perceived stress and smartphone addiction (mediation effect accounted for 33.3%, SE = 0.10, 95% CI = [0.10, 0.24]), and the first stage of the mediation process was significantly moderated by psychological capital (moderated mediation = − 0.01, SE = 0.01, 95%CI = [− 0.01, − 0.00]). Conclusions: Negative emotions plays a mediating role between perceived stress and smartphone addiction, and psychological capital plays an important moderating role in the first stage of the mediation process.